Resource Rents and their Impact on Institutional and Economic Development - Ian Keay (Queen's University, Department of Economics, 2007)
Over the twentieth century, Canada's energy, forestry, and mining industries played a substantial and increasing role in the growth and development of the aggregate economy. Despite the improving fundamentals that were underlying their increased contributions to the size, capital intensity, and productivity of the aggregate economy, the relative profitability and equity market performance of the resource industries deteriorated over the twentieth century. Without having to invoke entrepreneurial failure among the resource industries or equity market inefficiency, I am able to illustrate that falling relative output prices played the key role in a reconciliation of what, at first glance, appears to be a surprising relationship between the resource industries' fundamentals, resource rents, and equity market performance.
Keywords: N22; N52; Q20; Q32; 330; Rohstoffvorkommen; Investition; Wirtschaftswachstum; Rohstoffwirtschaft; Produktivität; Rentabilität; Wirtschaftsgeschichte; Kanada